Paul and the faithfulness of God - Wright, N. T. (Nicholas Thomas) (Minneapolis : Fortress Press, 2013)
"This text [v. 4] is printed in two book sections: First book comprises Parts I and II and frontmatter. Second book has Parts III and IV plus bibliography and indices. This highly anticipated two-book fourth volume in N.T. Wrights magisterial series, Christian Origins and the Question of God, is destined to become the standard reference point on the subject for all serious students of the Bible and theology. The mature summation of a lifetimes study, this landmark book pays a rich tribute to the breadth and depth of the apostles vision, and offers an unparalleled wealth of detailed insights into his life, times, and enduring impact. Wright carefully explores the whole context of Paul's thought and activity--Jewish, Greek and Roman, cultural, philosophical, religious, and imperial--and shows how the apostles worldview and theology enabled him to engage with the many-sided complexities of first-century life that his churches were facing. Wright also provides close and illuminating readings of the letters and other primary sources, along with critical insights into the major twists and turns of exegetical and theological debate in the vast secondary literature. The result is a rounded and profoundly compelling account of the man who became the worlds first, and greatest, Christian theologian"--Publisher description.
PART I. Paul and His World -- 1. Return of the runaway? -- 2. Like birds overhead : the faithfulness of the God of Israel -- 3. Athene and her owl : the wisdom of the Greeks -- 4. A cock for Asclepius : 'religion' and 'culture' in Paul's world -- 5. The eagle has landed : Rome and the challenge of empire -- PART II. The Mindset of the Apostle -- 6. A bird in the hand? : the symbolic praxis of Paul's world -- 7. The plot, the plan and the storied worldview -- 8. Five signposts to the apostolic mindset -- PART III. Paul's Theology -- 9. The one God of Israel, freshly revealed -- 10. The people of God, freshly reworked -- 11. God's future for the world, freshly imagined -- PART IV. Paul in History -- 12. The lion and the eagle : Paul in Caesar's empire -- 13. A different sacrifice : Paul and 'religion' -- 14. The foolishness of God : Paul among the philosophers -- 15. To know the place for the first time : Paul and his Jewish context -- 16. Sign of the new creation : Paul's aims and achievements.
Book 1 contains Part 1: Paul and his world and Part 2: The mindset of the apostle; book 2 contains Part 3: Paul's theology and Part 4: Paul in history.
Includes bibliographical references and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; God (Christianity) -- History of doctrines -- Early church, ca. 30-600.